2016
DOI: 10.3168/jds.2015-10162
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing individual differences in animal responses to a nutritional challenge: Toward improved robustness measures

Abstract: The aim of this paper was to explore the variation between individuals in the response to and recovery from a nutritional challenge, the repeatability of responses between lactation stages, and the use of shape-clustering methods to classify similar individuals. Sixteen dairy goats were exposed to a 2-d nutritional challenge (underfeeding) at 2 different stages of lactation. Each challenge consisted of a 7-d control period with standard total mixed ration (TMR), 2d of straw-only feeding, and a 10-d recovery pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…Review: Deciphering animal robustness nutritional challenges lasting 2 to 4 days, tracking performance and blood metabolites of animals before, during and after a shift from a standard feed to a very poor quality feed (Bjerre-Harpøth et al, 2012;Friggens et al, 2016). Both studies documented inter-animal variability in responses in dry matter intake and milk production which was largely related to pre-challenge levels.…”
Section: Friggens Blanc Berry and Puilletmentioning
confidence: 99%
See 3 more Smart Citations
“…Review: Deciphering animal robustness nutritional challenges lasting 2 to 4 days, tracking performance and blood metabolites of animals before, during and after a shift from a standard feed to a very poor quality feed (Bjerre-Harpøth et al, 2012;Friggens et al, 2016). Both studies documented inter-animal variability in responses in dry matter intake and milk production which was largely related to pre-challenge levels.…”
Section: Friggens Blanc Berry and Puilletmentioning
confidence: 99%
“…Højsgaard and Friggens (2010) showed that using multivariate time-series statistics to combine different mastitis indicators (electrical conductivity, somatic cell count and lactate dehydrogenase), a degree of infection index could be constructed. This approach has promise for combining indicators of 'the various things' that are key components of robustness (or at least robustness to a particular type of environmental perturbation), with different statistical and modelling approaches proposed (Sadoul et al, 2015b;Friggens et al, 2016). The key issue is to know which robustness components should be included in a given index and which measures contain information about these components.…”
Section: Managing Robustness: Measuring and Predictingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent developments in monitoring technologies allow the continuous recording of animal performance (Neethirajan, 2017). Although several studies have explored these technologies to study the impacts of perturbations on animal performance (Codrea et al, 2011;Munsterhjelm et al, 2015;Friggens et al, 2016), these technologies have not yet been used to develop a generic method that detects perturbations and that allows to quantify the animal's response to perturbations. Therefore, the objective of this study was to propose a data analysis and modelling procedure to detect the impact of perturbations in growing pigs and quantify the feed intake response in terms of resistance and resilience.…”
Section: Introductionmentioning
confidence: 99%